Debt aversion experiment: A replication with sophisticated participants - Kazunori Yakushiji; Jieyi Duan; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2024)
We conduct a replication experiment, with sophisticated student participants, of the three main treatments of the debt aversion experiment by Martínez-Marquina and Shi (2024). While participants in our experiment have chosen return maximizing strategies much more frequently than those in Martínez-Marquina and Shi (2024), our findings partially corroborate their observations that participants burdened with debt tend to forego, at least initially, the "certain and maximum profit investment opportunity" in favor of prioritizing debt repayment.
Keywords: C91; D91; G51; 330; Replication; Debt Aversion; Portfolio Allocation